Bentuk Distribusi Hujan Jam - Jaman Kabupaten Kampar Berdasarkan Data Satelit - Thessalonika Thessalonika; Yohanna Lilis Handayani; Manyuk Fauzi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Rainfall distribution is one of the parameters required for calculations of the design flood. The pattern of rainfall distribution is the mean of rainfall expressed in a graph that describe time function to variation in depth of rainfall. The pattern of rainfall distribution is obtained in two method, empirical method and averaging hourly rainfall data. The rainfall data used is obtained from TRMM JAXA in eight years (2009-2016) for Kampar Regency. In this research, the approach of distribution form between empirical methods with the hourly rainfall data average of TRMM to simplify the acquisition pattern of rainfall distribution. The empirical method used is Alternating Block Method (ABM), Modified Mononobe, and Tadashi Tanimoto. Based on TRMM rainfall data, that rainfall duration was dominated by one hours rainfall events. The analysis results for pattern of rainfall distribution approach of TRMM JAXA with empirical method shows that designed rainfall duration (3 to 8 hours) tends to approach Alternating Block Method (ABM) pattern.Keywords: Rainfall distribution, satellite rainfall data, Alternating Block Method, Modified Mononobe, Tadashi Tanimoto